2015
DOI: 10.1038/sj.bdj.2015.247
|View full text |Cite
|
Sign up to set email alerts
|

Use and knowledge of IOTN among GDPs in Scotland

Abstract: Overall use and knowledge of IOTN among GDPs in Scotland appears to still be low. More resources need to be directed towards improving both undergraduate and postgraduate orthodontic training with the focus on IOTN in particular.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 16 publications
0
6
0
2
Order By: Relevance
“…To date, the majority of research has evaluated IOTN in terms of scope for calibrating dental students 3,4 and the ability of GDPs and orthodontic specialists to use the index. [5][6][7] A study evaluating GDPs' knowledge and use of IOTN in Scotland found that of 231 participants, only 40% used IOTN to assess referral eligibility. 5 Half the participants reported a lack of training was a key barrier to use.…”
Section: Guidelines For Commissioning Dental Specialties Formentioning
confidence: 99%
See 1 more Smart Citation
“…To date, the majority of research has evaluated IOTN in terms of scope for calibrating dental students 3,4 and the ability of GDPs and orthodontic specialists to use the index. [5][6][7] A study evaluating GDPs' knowledge and use of IOTN in Scotland found that of 231 participants, only 40% used IOTN to assess referral eligibility. 5 Half the participants reported a lack of training was a key barrier to use.…”
Section: Guidelines For Commissioning Dental Specialties Formentioning
confidence: 99%
“…[5][6][7] A study evaluating GDPs' knowledge and use of IOTN in Scotland found that of 231 participants, only 40% used IOTN to assess referral eligibility. 5 Half the participants reported a lack of training was a key barrier to use. A further study assessing the ability of different types of dental registrants to provide an appropriate IOTN score found both Dental Foundation Trainees and GDPs achieved fair to poor agreement with experts.…”
Section: Guidelines For Commissioning Dental Specialties Formentioning
confidence: 99%
“…Nuspręsti, kada reikia nukreipti pacientą ortodontiniam gydymui, padeda ortodontinio gydymo reikalingumo indeksai. Jie taip pat padeda suskirstyti pacientus pagal gydymo reikalingumą [3][4][5][6]. Užsienio šalyse (Jungtinėje Karalystėje, Skandinavijoje) tokie indeksai naudojami tarp bendrosios praktikos gydytojų odontologų bei ortodontų kaip teisinis kriterijus siekiant ortodontinio gydymo finansavimo [5,7] Darbo tikslai: įvertinti Lietuvos gydytojų ortodontų ir ortodontijos specialybės gydytojų rezidentų žinias apie ortodontinio gydymo reikalingumo indeksą ir indekso taikymą klinikinėje praktikoje bei palyginti, kaip Lietuvos sveikatos mokslų universiteto Medicinos akademijos Odontologijos fakulteto (LSMU MA OF) 5 kurso odontologijos studentai ir Lietuvos gydytojai ortodontai vertina ortodontinio gydymo reikalingumo indekso IOTN estetinį komponentą.…”
Section: įVadasunclassified
“…Gydytojų ortodontų dantų būklės komponento vertinimo balas buvo ypač žemas. Tik 7% ortodontų turėjo vidutinį suderinamumą su "auksiniu" standartu, šie duomenys panašūs į Škotijoje atlikto tyrimo, kuriame 10,5% respondentų Cohen'o Kappa koeficientas buvo didesnis už 0,61 [5]. Lyginant rezultatus tarp gydytojų ir studentų, rezultatai buvo patenkinami.…”
Section: Diskusijaunclassified
“…A similar study in 2015 by Puri et al showed that 74% of GDPs felt they would bene t from more training in the use of IOTN. 10 Jawad et al 2016 further evidenced this nding by highlighting a need for greater support in training and resources to help GDPs use the IOTN more accurately. 11 To address the need for increased resources and support for GDPs the British Orthodontic Society developed the "Easy IOTN" mobile app available on both Apple and Android devices in 2016.…”
mentioning
confidence: 99%